Ethics and global environmental policy cosmopolitan conceptions of climate change - Harris, Paul G.; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2011)
This collection of provocative essays re-evaluates the world's failed policy responses to climate change, in the process demonstrating how cosmopolitan ethics can inform global environmental governance.
1. Introduction : cosmopolitanism and climate change policy / Paul G. Harris -- 2. Climate justice as globalized responsibility : mitigation, adaptation and avoiding harm to others / Steve Vanderheiden -- 3. Climate change and the cosmopolitan responsibility of individuals : policy / Vanguards Nigel Dower -- 4. Individual responsibility and voluntary action on climate change : activating agency / Jennifer Kent -- 5. Cosmopolitan solutions "from below" : climate change, international law and the capitalist challenge / Romain Felli -- 6. Sharing the burdens of climate change : environmental justice and qualified cosmopolitanism / Michael W. Howard -- 7. Cosmopolitanism and hegemony : the United States and climate change / Robert Paehlke -- 8. Overcoming the planetary prisoners' dilemma : cosmopolitan ethos and pluralist cooperation / Philip S. Golub and Jean-Paul Maréchal -- 9. Cosmopolitan diplomacy and the climate change regime : moving beyond international doctrine / Paul G. Harris.
Includes bibliographical references and index.
Keywords: Environmental policy -- Moral and ethical aspects; Environmental ethics; Electronic books